(untitled) (Journal of the College of Education for Women, 2020)
Samuel Beckett’s Happy Days (1961) clearly portrays a lack of communication among the characters of the play which refers to the condition of modern man. This failure of communication led Samuel Beckett to use a lot of pauses and silences in all plays written instead of using words. To express the bewilderment of the modern man during the 20th century, Beckett adopts the use of no language strategy in the dramatic works. After World War II, people were without hope, religion, food, jobs, homes, or even countries. Beckett gave them a voice. He used a dramatic language out of everyday things, in which silence was part of the syntax as a poetic repetition. Language is no more important to the modern man; instead, he used silence to express his feelings. For him, silence is more powerful than the words themselves. That’s why; long and short pauses can be seen throughout all Beckett’s plays. In this play, the characters chose not to communicate; instead, they kept silent because they failed to interact with each other or even with themselves. The nature of this study is qualitative and objective; it textually analyzes the text to show the state of the modern man during 20th century. As a conclusion, one can say that Beckett’s use of pauses and silences was to express the bewilderment of the modern man and the inner conflict inside of him. Moreover, the modern man has lost his communication with other people as a result of that conflict.